2019
DOI: 10.1002/hbe2.147
|View full text |Cite
|
Sign up to set email alerts
|

Humanization of robots: Is it really such a good idea?

Abstract: The aim of this review was to examine the pros and cons of humanizing social robots following a psychological perspective. As such, we had six goals. First, we defined what social robots are. Second, we clarified the meaning of humanizing social robots. Third, we presented the theoretical backgrounds for promoting humanization. Fourth, we conducted a review of empirical results of the positive effects and the negative effects of humanization on human–robot interaction (HRI). Fifth, we presented some of the pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 115 publications
0
28
0
Order By: Relevance
“…The latter is possibly inspired by science fiction media, as we tend to ascribe higher abilities to more naturalistic robots (Walters et al, 2008) and spontaneously apply social expectations to computers (Nass and Moon, 2000), but we cannot anticipate what robots are capable of, as they might not have human morals and at the same time superhuman capabilities. Even if robots looked exactly like humans, as long as we still know or, more accurately, believe that they are robots, we would probably experience an uncanny feeling, as happening in HBO's Westworld [see also Giger et al (2019) for an overview of the benefits and drawbacks of humanizing robots].…”
Section: Implications For the Uncanny Valley Hypothesismentioning
confidence: 99%
“…The latter is possibly inspired by science fiction media, as we tend to ascribe higher abilities to more naturalistic robots (Walters et al, 2008) and spontaneously apply social expectations to computers (Nass and Moon, 2000), but we cannot anticipate what robots are capable of, as they might not have human morals and at the same time superhuman capabilities. Even if robots looked exactly like humans, as long as we still know or, more accurately, believe that they are robots, we would probably experience an uncanny feeling, as happening in HBO's Westworld [see also Giger et al (2019) for an overview of the benefits and drawbacks of humanizing robots].…”
Section: Implications For the Uncanny Valley Hypothesismentioning
confidence: 99%
“…Secondly, if some duties are to be performed by a robot (which might interact with human, including making decisions on behalf of the employer), will such robot perform functions entrusted to it considering specific ethical principles [ 4 , 31 ]. As opposed to a human, a robot is deprived of any emotions [ 4 , 5 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Anthropomorphism helps people predict the moral and emotional states of robots and therefore influences humans' perceptions of and behaviors toward service robots (L. Lu et al, 2019;Mara & Appel, 2015;Murphy et al, 2019). For example, the use of service robots was found to decrease the loneliness of older people and the anxiety of hospitalized children (Giger et al, 2019). It is also found that the more robots appear and behave like humans, the more meaningful interactions between humans and robots can become (Wirtz et al, 2018).…”
Section: Service Recovery Entities and Recovery Satisfactionmentioning
confidence: 99%